Dharmic Religions and Health: A Holistic Analysis of Global Health Literature Related to Hinduism, Buddhism, Sikhism and Jainism - Senel, Engin (Journal of religion and health, 2019)
Bibliometrics and scientometrics are popular and novel disciplines providing information in publication trends in a certain academic field. Although there has been an increasing popularity in bibliometric studies, a limited number of reports have been published in religion and health literature. In this study, to the best of our knowledge we aimed to perform a first bibliometric analysis in the health literature related to Dharmic religions, Hinduism, Buddhism, Sikhism and Jainism. We found a total of 655 health articles related to Dharmic religions as we searched Web of Science databases. The United States of America (USA) ranked first in Health and Hinduism literature with 62 documents followed by India, the UK and Bangladesh (n = 40, 33 and 6, respectively). A detailed keyword analysis revealed that the most used keywords in the field of Hinduism and health were "Hinduism," "religion," "spirituality" and "Islam." The USA was also the leading county in the literature of Buddhism and Health with 159 articles (32.78%) and followed by Thailand, the UK and China (10.72, 6.8 and 6.39%, respectively). The Journal of Religion and Health was noted to be the most prolific source in this field. We found that the developing countries such as India, Thailand, Singapore and Taiwan were found to be included in the most productive countries list on the contrary to previous bibliometric studies in health and religion field.